PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN FOOD AND BEVERAGE SERVICE FOX HOTEL PEKANBARU - Elvina Sovia Laurence; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
A hotel is a building that is used as a sleeping room, a room for eating and drinking, a venue for various events such as weddings, meetings, birthdays, etc. There are various 4-star hotels in Pekanbaru, so the hotel class must have a good strategy and service to attract visitors, a safe and peaceful working environment can affect the feelings of the hearts of employees when doing work, so as to ensure good performance and delight guests. In this study, researchers conducted a study on the food and beverage department at the Fox Hotel Pekanbaru. The population of this study used 10 people with a saturation sample, that is, the entire population was selected. Data collection methods using questionnaires, observation and documentation. The method used in this study is classical hypothesis testing, hypothesis testing, multiple linear regression analysis, and coefficient of determination using SPSS 25. According to the results of the study, the work environment has a positive and significant effect on the significance level F